Sense and Sensitivity: An Argument Against Reporting Multiple Net Present Values - Frikk Nesje; Moritz A. Drupp; Mark C. Freeman; Ben Groom (CESifo GmbH, 2024)
We critically assess an almost universal Benefit-Cost Analysis (BCA) practice. In addition to the central Net Present Value (NPV), analysts frequently also report multiple additional values in what is commonly referred to as 'NPV sensitivity analysis'. This practice is generally justified with reference to the future net benefits to the asset being risky, or because the correct discounting model is difficult to identify. We explain why, despite the fact that this is recommended as best practice across multiple prestigious and influential sources, the reporting of more than one NPV either lacks sufficient theoretical support or reflects decisions taken at an inappropriate level within the organizational hierarchy. As a consequence, this practice may confuse decision-makers more than help them. We illustrate this point in relation to a number of current guidelines across the public and private sectors and with particular focus on the US Environmental Protection Agency's latest estimates of the Social Cost of Carbon.
Keywords: H43; G31; L51; Q51; Q54; 330; benefit-cost analysis; net present value; sensitivity analysis; social cost of carbon; regulatory analysis